Contrast enhancement in 1p/19q-codeleted anaplastic oligodendrogliomas is associated with 9p loss, genomic instability, and angiogenic gene expression. Issue 5 (18th December 2013) - Reyes-Botero, German; Dehais, Caroline; Idbaih, Ahmed; Martin-Duverneuil, Nadine; Lahutte, Marion; Carpentier, Catherine; Letouzé, Eric; Chinot, Olivier; Loiseau, Hugues; Honnorat, Jerome; Ramirez, Carole; Moyal, Elisabeth; et al.
Abstract: Background: The aim of this study was to correlate MRI features and molecular characteristics in anaplastic oligodendrogliomas (AOs). Methods: The MRI characteristics of 50 AO patients enrolled in the French national network for high-grade oligodendroglial tumors were analyzed. The genomic profiles and IDH mutational statuses were assessed using high-resolution single-nucleotide polymorphism arrays and direct sequencing, respectively. The gene expression profiles of 25 1p/19q-codeleted AOs were studied on Affymetrix expression arrays. Results: Most of the cases were frontal lobe contrast-enhanced tumors (52%), but the radiological presentations of these cases were heterogeneous, ranging from low-grade glioma-like aspects (26%) to glioblastoma-like aspects (22%). The 1p/19q codeletion ( n = 39) was associated with locations in the frontal lobe ( P = .001), with heterogeneous intratumoral signal intensities ( P = .003) and with no or nonmeasurable contrast enhancements ( P = .01). The IDH wild-type AOs ( n = 7) more frequently displayed ringlike contrast enhancements ( P = .03) and were more frequently located outside of the frontal lobe ( P = .01). However, no specific imaging pattern could be identified for the 1p/19q-codeleted AO or the IDH -mutated AO. Within the 1p/19q-codeleted AO, the contrast enhancement was associated with larger tumor volumes ( P = .001), chromosome 9p loss and CDKN2A loss ( P = .006), genomic instability ( P = .03), and angiogenesis-related gene expression ( P < .001), particularly for vascular endothelial growth factor A and angiopoietin 2. Conclusion: In AOs, the 1p/19q codeletion and the IDH mutation are associated with preferential (but not with specific) imaging characteristics. Within 1p/19q-codeleted AO, imaging heterogeneity is related to additional molecular alterations, especially chromosome 9p loss, which is associated with contrast enhancement and larger tumor volume.